2019
DOI: 10.1002/app.48029
|View full text |Cite
|
Sign up to set email alerts
|

Novel thin‐film nanocomposite membrane with water‐soluble polyhydroxylated fullerene for the separation of Mg2+/Li+ aqueous solution

Abstract: Despite the prosperity of membrane technology, the separation efficiency for Mg 2+ /Li + mixture is still far from satisfactory. Herein, a novel thin-film nanocomposite (TFN) membrane was developed by loading polyhydroxylated fullerene (PHF) via interfacial polymerization. The effects of the PHF dosages on the as-developed membranes were investigated comprehensively by XPS, SEM, AFM, contact angle measurements, as well as nanofiltration tests. The results revealed the TFN membrane containing 0.01% (w/v) PHF ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…A novel NF membrane has been recently investigated by doping water-soluble polyhydroxylated fullerene onto a polyamide layer during the polymerization process between PIP and TMC on the PES base membrane, as shown in Fig. 15d [207]. Note that the water permeation of the membranes increased by 39.2%, and the membrane showed high antifouling properties.…”
Section: Nanofiltration Membrane Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…A novel NF membrane has been recently investigated by doping water-soluble polyhydroxylated fullerene onto a polyamide layer during the polymerization process between PIP and TMC on the PES base membrane, as shown in Fig. 15d [207]. Note that the water permeation of the membranes increased by 39.2%, and the membrane showed high antifouling properties.…”
Section: Nanofiltration Membrane Techniquementioning
confidence: 99%
“…range in brine is 5-90. Enhancing the applied voltage can effectively improve the separation efficiency and recovery rate Figure 15 Preparation schematic diagram of a DAPP/TMC hollow positively charged NF membrane [206]; b PEI/TMC high positively charged NF membrane [201]; c M-CNTs grafted PIP/TMC hollow NF membrane [209]; d polyhydroxylated doped PIP/TMC NF membrane [207]; e BPEI/TMC positively charged NF membrane [25]; and f double-Janus composite NF membrane [208]. [216].…”
Section: Electrodialysis Technologymentioning
confidence: 99%
“…Whereas, the apolar and hydrophobic character of fullerene can facilitate ENM recovery after remediation. Currently, most NF membranes are thin-film composites (TFC), and their ability to selectively separate ion metals (Li + , Mg 2+ , Pb 2+ , Cd 2+ , Zn 2+ , and Ni 2+ ) from aqueous media has been widely investigated [124,125]; however, to date, it has been synthesized only one membrane that exhibited a high Mg 2+ /Li + separation factor suggesting its potential application in treatment of Li contaminated seawater [22]. CNTs are one-dimensional fibrous nanomaterials formed by a single or multiple rolled layer, which assumes the structure of a hollow and cylindrical tube [126].…”
Section: Hybrid Nanocompositesmentioning
confidence: 99%
“…To date, experimental studies established that ENMs can be employed to efficiently restore different marine environmental matrices [ 21 , 22 , 23 ], reducing the impact of toxic chemicals, thus, preserving marine biodiversity, ecosystem functioning and services. However, as such, they are applied as primary ENMs to the environment and the balance between benefits and risks associated with their use is still under debate [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…With 0.01% (w/v) fullerenol, the membrane revealed excellent antifouling ability, stable and high efficiency in Mg 2+ /Li + separation with a high separation factor of 13.1. These membranes formed were suggested to have great potential in the recovery of Li + from seawater [145]. Liu et al reported C 60 grafted graphene oxide membranes with a fixed interlayer spacing around ∼12.5 Å [146].…”
Section: Fullerene-based Polymer-nanocomposite Membranesmentioning
confidence: 99%